Present status of major diseases of sunflower in Northern East Dry Zone of Karnataka: Present status of major diseases of sunflower in Northern East Dry Zone of Karnataka - POORNIMA; VIKAS V KULKARNI; VIJAYAKUMAR GHANTE; M R UMESH (Journal of Oilseeds Research, 2023)
A Fixed plot survey was conducted to assess the severity of Alternaria leaf blight, Sunflower necrosis disease, Powdery mildew and Sunflower leaf curl disease during Rabi 2020-21 and Kharif 2021 in Raichur, Koppal and Gulbarga districts of North Eastern Karnataka. The survey results revealed that disease severity was noticed in all locations surveyed. In surveyed area, the PDI of Alternariaster leaf spot was ranged from 42.2 % to 72.8 %. Sunflower necrosis disease incidence ranged from 3.5 to 21.9%. Whereas, during rabi 2020-21 powdery mildew PDI ranged between 30.0 to 75 per cent and leaf curl ranged between 0 to 18.7 per cent in three districts surveyed.